ANALISIS FINANSIAL PEMANFATAN DAN PENGOLAHAN DAUN JERUJU (Acanthus ilicifolius L) MENJADI BERBAGAI PRODUK OLAHAN (Financial Analysis of utilization and Processing of Jeruju Leaves (Acanthus ilicifolius L) Becomes Various Products) - Eko Prayogo; Agus Purwoko; Kansih Sri Hartini (Program studi Kehutanan USU, 2016)
Jeruju is one of mangrove commodities that can be found at various location including in Sei Nagalawan village. Most of the utilization of jeruju leaves still conventional and subsistence .jeruju utilization is still limited for the leaves and roots. At household jeruju leaves processing has been in Sei Nagalawan village it was process then into jeruju kerupuk and jeruju tea. According the study aim to know finansial feasibility leaves processing household jeruju, to know processing of jeruju leaves becomes various products, the financial feasibility and to know added value jeruju leaves in every production process in Sei Nagalawan village. This research was done in March 2015. Sampling was done by purposive and the method used in the form of cost and revenue analysis, RC Ratio analysis, Break event point analysis, and Added value analysis. This research showed that financially, jeruju kerupuk enough being product because its RC ratio more than one (1,17) and therefore jeruju tea enough being product because its RC ratio more than one (2,14). BEP total of jeruju kerupuk is 31 packs while jeruju tea is 7 packs and BEP price is about Rp 5.200,- per pack for jeruju kerupuk and Rp 4.700,-/ packs for jeruju tea. Added value for jeruju kerupuk is Rp 49.577,-/kg, and for jeruju tea is Rp 81.150,-/kg. Market opportunity is still possible, because it's still rare in market. Strategic area of Sei Nagalawan village will support access to market.Key words : Jeruju Leaves, financial analysis, added value, Jeruju Kerupuk product, Jeruju Tea.